AB mix-NPK fertilizer combination effect on corn plants growth using Nutrient Film Technique - Harsela, Chiska Nova (International Journal Labs, 2024)
Corn (Zea mays) is one of the important food crops in Indonesia. Efforts to increase corn production continue to be made, one of which is by using appropriate fertilizer. The aim of this research is to determine the effect of the combination of AB Mix and NPK fertilizers on the growth of corn (Zea mays) plants using the NFT hydroponic system. This study used qualitative research methods. The data collection technique in this research is literature study, while data analysis is carried out in three stages, namely data reduction, data presentation and drawing conclusions. The findings from the research show that the use of a combination of AB mix and NPK fertilizers in the growth of corn (Zea mays) using the Nutrient Film Technique (NFT) technique has a significant impact. Using these two types of fertilizer together increases the growth of corn plants by increasing plant height, number of leaves, and development of the root system. In addition, with optimal nutrient availability from the fertilizer combination through the NFT technique, corn production is increased efficiently. The findings show the potential for using a combination of AB mix and NPK fertilizers in increasing agricultural yields.